Recreational alcohol use induces changes in the concentrations of choline-containing compounds and total creatine in the brain: a 1H MRS study of healthy subjects - Tunç-Skarka, Nuran; Weber-Fahr, Wolfgang; Ende, Gabriele (Magnetic resonance materials in physics, biology and medicine, 2015)
ObjectiveIt has previously been reported that even social alcohol consumption affects the magnetic resonance spectroscopy (MRS) signals of choline-containing compounds (tCho). The purpose of this study was to investigate whether the consumption of alcohol affects the concentrations of the metabolites tCho, N-acetylaspartate, creatine, or myo-inositol and/or their T 2 relaxation times.Materials and methods 1H MR spectra were obtained at 3 T from a frontal white matter voxel of 25 healthy subjects with social alcohol consumption (between 0 and 25.9 g/day). Absolute brain metabolite concentrations and T 2 relaxation times of metabolites were examined via MRS measurements at different echo times. Metabolite concentrations and their T 2 relaxation times were correlated with subjects’ alcohol consumption, controlling for age.ResultsWe observed positive correlations of absolute tCho and phosphocreatine and creatine (tCr) concentrations with alcohol consumption but no correlation between any metabolite T 2 relaxation time and alcohol consumption.ConclusionsThis study shows that even social alcohol consumption affects the concentrations of tCho and tCr in cerebral white matter. Future studies assessing brain tCho and tCr levels should control for the confounding factor alcohol consumption.